DESIGN OF EDUCATIONAL RECYCLING WASTE MANAGEMENT VIDEO GAME FOR CHILDREN - Setyawati, Endang; Paath, David Kristian; Komala, Evelyne Kristiani (LPPM STMIK Dharmapala Riau, 2020)
As time goes by, the earth has undergone many changes, many of which have happened, from natural changes to human lifestyle. Many natural disasters occur as a result of the development of human lifestyles, such as floods caused by littering and piling up. Littering is one of the causes of flooding, therefore it is necessary to build awareness of society, especially children as the next generation. The purpose of